Lesbian and Gay Rights - NALGO poster, 1984 (1984)
1984 1960-2000 "Lesbian and Gay Rights - NALGO poster, 1984" [T0594.jpg], 1984 National and Local Government Officers Association poster Lesbian and Gay Rights - NALGO fighting against prejudice.